Effects of cadmium-resistant plant growth-promoting rhizobacteria and Funneliformis mosseae on the cadmium tolerance of tomato (Lycopersicon esculentum L.). Issue 5 (15th April 2020) - Li, Yuanyuan; Zeng, Jiahui; Wang, Shizhong; Lin, Qingqi; Ruan, Dishen; Chi, Haochun; Zheng, Mengyuan; Chao, Yuanqing; Qiu, Rongliang; Yang, Yanhua
Abstract: Microorganisms are used to alleviate heavy metal stress in plants cultivated in contaminated fields. However, the relevant mechanisms have been rarely explored. The goal of this study was to investigate effects of arbuscular mycorrhizal fungus Funneliformis mosseae and two Cd-resistant bacterial strains ( Enterobacter sp. EG16 and Enterobacter ludwigii DJ3) on growth and Cd tolerance of tomato when applied with different inoculation strategies (single or dual) and Cd concentrations (50 and 100 mg kg −1 ). Better plant growth was observed in mycorrhizal alone or combined treatments. In F . mosseae and EG16 co-inoculation treatment, shoot and root dry weight were 119–154% and 91–173% higher than those of the control, respectively. Higher bacterial and mycorrhizal colonization rate and root Cd concentration were also found in this treatment. However, the decrease of shoot Cd concentration and translocation factor values indicated this treatment was effective in improving Cd tolerance of the host plants. In addition, the increase in soil pH and decline in bioavailable Cd in the rhizosphere might be partly involved in reduction of Cd accumulation in plants. Our results suggest that co-inoculation with suitable microorganisms is important in plant growth and tolerance to Cd in Cd-contaminated soil.